Promoting Contextual Teaching and Learning Method of EFL Students in Post Pandemic for 21st Century Skill: Teachers’ Perception - Vina Fathira; M. Zaim; Hermawati Syarif; Yetty Zainil (Universitas Muhammadiyah Semarang, 2022)
Contextual teaching and learning is one of the best method to gain the real experiences for EFL students in post pandemic for promoting learning method of 21st century skill. The aim of this study is to find out the teachers’ perception for promoting contextual teaching and learning for English as Foreign Language. The method of this research was quantitative. In collecting data, the researchers were set a questionnaire about 12 items and distributed it to the teachers in any education level by Google form. After getting the data, the researcher counting the percentage of the respondents’ answer and analyze based on the needs of contextual teaching and learning. The result showed that teachers’ perception for language learning that contextual teaching and learning is very valuable for the students in develop many things like knowledge, curiosity, information and many others for 21st century skill in post pandemic. However, there was only a limited lack of promoting contextual teaching and learning for teaching English, like not providing new knowledge. In conclusion, the teachers’ perception on contextual teaching and learning should be applied in the real classroom to explore more the knowledge in contextual meaning